Within-School Tracking in South Korea : An Analysis Using Pisa 2003 - Macdonald, Kevin; Patrinos, Harry Anthony (2012)
The 2003 PISA Korea sample is used to examine the association between within-school ability tracking and mathematics achievement. Estimates of a variety of econometric models reveal that tracking is positively associated with mathematics achievement among females and that this association declines for higher achieving females. No evidence of an association between males and tracking is detected. While this association for females cannot be interpreted as a causal effect, the presence of a measurable association indicates the need for further research on tracking in Korea with a particular focus on gender differences.